Analysis of the Relationship between Capital Structure and Financial Performance in Indra Karya Sewing Services Business - Zai, Yumelsin; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
This article analyzes the relationship between capital structure and financial performance in the Indra Karya Tailor sewing service business in Sendang Waru Market, Pringapus, Semarang Regency. This study uses a qualitative approach with in-depth interviews with five respondents, consisting of business owners, employees, and regular customers. Data analysis was conducted using thematic techniques to identify relevant patterns and findings. The results of the study indicate that an effective capital structure is managed through a balance between equity and loans, diversification of raw material sources, and control of operational costs to maintain financial stability. The strategy to improve business performance focuses on improving product quality, design innovation, and responsive service to customer needs. High customer satisfaction has a direct impact on loyalty and increased revenue, which supports long-term business sustainability. As a recommendation, business owners are advised to optimize their capital structure by reducing dependence on short-term loans, expanding their supplier network to reduce production costs, and improving customer service through a more flexible and interactive ordering system. With this strategy, business competitiveness can be strengthened in the competitive sewing service industry.